Detoxification of Chromium (VI) Ions in Aqueous Solution via Adsorption by Raw and Activated Carbon Prepared from Sugarcane Waste - Andrew, Ofudje Edwin; Olushola, Awotula Ayodeji; Dada, Williams Olawale; Opeoluwa, Oladipo Gabriel (Covenant Journal of Physical and Life Sciences, 2014)
The use of raw and modified agricultural waste primed from sugarcane as sorbents for the removal of Cr(VI) ions from aqueous solution were examined in a batch process. FT-IR analysis revealed that –OH, –NH, C–O and aromatic rings functional groups were involved in the sorption process. Sorption of Cr(VI) on raw and modified biomass were studied as a function of pH, contact time, initial metal concentration and temperature. Maximum experimental conditions were obtained to be initial metal concentration of 50 mg/L, temperature of 45oC, contact time of 60 minutes and pH of 2.0. The kinetics studies indicated that the sorption pattern for the sorption of Cr(VI) ions by raw sugarcane waste and acid modified sugarcane waste followed Ho’s-pseudo-second-order model, while that of carbonized acid modified sugarcane waste was well fitted by Largergren pseudo-first model. Thermodynamic parameters suggested the feasibility, spontaneity, endothermic and randomness of the sorption process. Thus, biomass from sugarcane waste can be deployed in the detoxification of Cr(VI) ions from aqueous solution. Keywords: Adsorption, Chromium, Kinetics, Pollution and Thermodynamic.